2020
DOI: 10.1159/000508510
|View full text |Cite
|
Sign up to set email alerts
|

A New Two-Step Anesthesia for 23- or 25-Gauge Vitrectomy Surgery: A Prospective, Randomized Clinical Trial

Abstract: Objective: To investigate the safety and efficacy of topical anesthesia combined with subconjunctival anesthesia (termed two-step anesthesia) for 23- or 25-gauge pars plana vitrectomy or other posterior segment surgery. Methods: Patients (n = 90) requiring 23-/25-gauge vitrectomy or other posterior segment surgery were randomized into 3 groups. Group 1 received peribulbar anesthesia, group 2 received retrobulbar anesthesia and group 3 received two-step anesthesia. A 5-point visual analog pain scale (VAPS) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The majority of eye surgeries are performed under regional anesthesia. This type of anesthesia includes different sub-types, such as topical anesthesia [13][14][15] , subconjunctival anesthesia [16][17][18] , retrobulbar anesthesia, peribulbar anesthesia, sub-Tenon's anesthesia [9,[19][20] , medial canthus epiescleral anesthesia [21] and facial nerve block. Topical anesthesia has become a common form of anesthesia; however, it requires that the surgery is performed quickly and efficiently to minimize stress on the patients [22] , patient cooperation [23] , experienced surgeon [10] and it doesn't provide the same level of pain relief as peribulbar anesteshia [24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of eye surgeries are performed under regional anesthesia. This type of anesthesia includes different sub-types, such as topical anesthesia [13][14][15] , subconjunctival anesthesia [16][17][18] , retrobulbar anesthesia, peribulbar anesthesia, sub-Tenon's anesthesia [9,[19][20] , medial canthus epiescleral anesthesia [21] and facial nerve block. Topical anesthesia has become a common form of anesthesia; however, it requires that the surgery is performed quickly and efficiently to minimize stress on the patients [22] , patient cooperation [23] , experienced surgeon [10] and it doesn't provide the same level of pain relief as peribulbar anesteshia [24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent studies have shown that local anesthetics that include lignocaine , amethocaine and bupivacaine are effective in providing topical and local anesthesia for intraocular surgery and Instillation of these local anesthesia decreases intraocular pressure (IOP) transiently . 12,8,5,13 As the duration of anesthesia and analgesia is very brief by these drugs , it requires repeat instillation of drops in the conjuctival sac after every 30 minutes but long-term use of these topical drugs is associated with ocular surface toxicity as they contain preservatives like benzalkonium chloride Most of the patients were in their fifth and sixth decade of life when they underwent 23 gauge three port pars removal of sillicone oil. The peribulbar technique for local anesthesia is a type of block that has been introduced and developed as ocular and periocular anesthetic technique for surgical procedures recently.…”
Section: Discussionmentioning
confidence: 99%
“…The peribulbar technique for local anesthesia is a type of block that has been introduced and developed as ocular and periocular anesthetic technique for surgical procedures recently. 7,8,4 The needle for peribulbar block is entered directly and is much shorter in length as compared to the previous technique of retro bulbar block as the later is associated with risk of complications like perforation of the globe and damage to optic nerve. The use of 26G ,25 mm needle for peribulbar block is much safer and this modified technique is the use of 23G needle that is associated with effective block and less rate of comlications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that relying solely on topical analgesia may not achieve ocular akinesia and requires special attention, particularly in macular surgery. [64,65] In cases of general anesthesia, the use of nitrous oxide (N 2 O) should be avoided. Given the potential for pain during the procedure, alternative analgesics, including opioids, should be considered.…”
Section: Strabismus Surgerymentioning
confidence: 99%